The influence of received integration efforts on immigrants’ adaptation and integration in Norway - Mateus, Maria Madalena Ferrão (2017)
The western world is registering an unprecedented number of people moving through borders to settle in a new country. The process of adaptation that occurs has been consistently study, however how the role of majority members in this process effects immigrants needs further attention. With the creation of a new scale – Received Integration Efforts Scale (RIES) -, I intend to contribute to close this gap. Furthermore, I analyse the causality between RIES, acculturation strategies, and sociocultural and psychological well-being. All in all, the results suggest that the higher the perception of participants in receiving help from Norwegians, specifically the received social inclusion integration efforts (RSIIE) and the received sociostructurally integration efforts domains (RSIE), the more they chose integration or assimilation strategies and the more they feel life satisficed and sociocultural adapted. Hence these findings emphasize the importance of majority members’ active efforts on immigrants’ adaptation and integration in Norway.